Neutron Characterization of BNCT Water Phantom Based on Kartini Research Reactor Using PHITS - Vika Hutaria; Susilo Susilo; Yohannes Sardjono (Indonesian Journal of Physics and Nuclear Applications, 2019)
Boron Neutron Capture Therapy (BNCT) is a therapy that utilizes the interaction of thermal neutrons with a boron-10 core that produces alpha particles and lithium nuclei. The result of this boron reaction has high linear energy transfer (LET). BNCT has an advantage over other radiation therapy in that it has a high selectivity level. This research was run using PHITS simulation to find out the value of neutron flux spread over a water phantom. The conclusion of the research is the distribution of neutron flux in the water phantom without boron is higher the the distribution of neutron flux in the water phantom containing boron